A hydrophobic biochar composite material and preparation method thereof
By modifying the surface of biochar with copolymers of sulfobetaine and acrylamide, the problem of hydrophilic functional groups limiting when biochar is adsorbed with hydrophobic pollutants is solved, and its adsorption effect is significantly improved, especially when treating water bodies containing perfluorocarbons.
Patent Information
- Application Number
- CN202310558494.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-17
AI Technical Summary
Existing biochar materials are limited by hydrophilic functional groups when adsorbing hydrophobic pollutants, and cannot effectively improve their hydrophobicity and adsorption effects.
By modifying the surface of biochar with copolymers of sulfobetaine and acrylamide, its hydrophilicity is changed and the adsorption ability to hydrophobic pollutants is improved.
The adsorption and removal effect of biochar on hydrophobic pollutants has been significantly improved, especially when treating water bodies containing perfluorochemicals, the adsorption amount has increased by more than 140%.
Smart Images

Figure CN116510690B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental new functional materials, and in particular relates to a hydrophobic biochar composite material and a preparation method thereof. Background Art
[0002] Perfluorinated compounds (PFASs) have been widely used in industry over the past few decades, but are ubiquitous in the environment due to their chemical persistence. Exposure to PFASs poses serious health risks, such as liver and kidney cancer, and therefore this class of compounds is now considered a priority pollutant. Among the methods currently used to remove PFCs, adsorption is considered one of the most suitable technologies.
[0003] Biochar has an adjustable specific surface area and pore structure, and its surface has rich functional groups. It can be obtained by high-temperature pyrolysis of various biomass materials. The raw materials for preparation are widely available, and it is a low-cost, widely available and environmentally friendly material. The surface of biochar is rich in oxygen-containing functional groups such as -COOH, -CHO, and -OH, which makes biochar have a good adsorption effect on many substances. However, these oxygen-containing functional groups are highly hydrophilic and are subject to certain limitations when adsorbing hydrophobic substances. Therefore, how to improve the hydrophobicity of biochar is of great significance for the effective removal of hydrophobic pollutants.
[0004] Through the above analysis, the problems and defects of the existing technology are as follows: the oxygen-containing functional groups such as -COOH, -CHO, -OH, etc. rich on the surface of biochar are hydrophilic groups. When adsorbing hydrophobic pollutants, the hydrophilicity and hydrophobicity between the two will hinder the adsorption process, affecting the removal effect of biochar on hydrophobic pollutants. The existing modification technology mainly improves the adsorption performance of biochar by changing the content and type of ash and functional groups of biochar and improving the pore structure of biochar. However, these modification technologies cannot change the hydrophobicity of biochar. Therefore, the existing modification technology cannot significantly improve the removal effect of biochar on hydrophobic pollutants. There is no technical report on the scheme for preparing hydrophobic biochar materials in the prior art.
[0005] The difficulty in solving the above problems and defects is that the adsorption of hydrophobic pollutants involves the hydrophobic interaction between biochar and pollutants. The stronger the hydrophobicity of biochar, the stronger the hydrophobic interaction between biochar and pollutants, and the better the adsorption effect. Although there are many modification technologies for the physical and chemical properties of biochar, they are mainly based on changing the pore structure of biochar and introducing hydrophilic groups. Existing modification technologies cannot improve the hydrophobicity of biochar.
[0006] The significance of solving the above problems and defects is that it is beneficial to improve the adsorption effect of biochar on hydrophobic pollutants. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a hydrophobic biochar composite material and a preparation method thereof.
[0008] The present invention is achieved by providing a hydrophobic biochar composite material, wherein the hydrophobic biochar composite material comprises biochar, and the surface of the biochar is modified with a copolymer of sulfobetaine and acrylamide.
[0009] The preparation method of the cationic polyacrylamide modified biochar composite material comprises the following steps:
[0010] Step 1, preparing a mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide;
[0011] Step 2, adding biochar to the mixed solution obtained in step 1 to obtain a black suspension;
[0012] Step 3, passing nitrogen gas into the black suspension obtained in step 2 for half an hour;
[0013] Step 4, adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to the black suspension obtained in step 3 to react to obtain a hydrophobic biochar composite material;
[0014] In step 1, in the mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide, the mass volume ratio of acrylamide to water is 10 g to 20 g:100 mL, and the mass volume ratio of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide to water is 10 to 40 g:100 mL;
[0015] In step 2, the mass volume ratio of the biochar and the mixed solution is 10-20 g:100 mL; after mixing, the mixture is stirred at 20° C. to 40° C. at a rotation speed of 160 rpm to 180 rpm for 6 to 24 hours.
[0016] In step 3, the reaction is carried out by introducing 100 mL to 200 mL / min of nitrogen into the mixed solution and stirring at 50 to 60° C. at a rotation speed of 120 rpm to 180 rpm for 0.5 to 2 h;
[0017] In step 4, the mass volume ratio of the ammonium persulfate to the black suspension is 2 mg-20 mg:100 mL, the mass volume ratio of the N,N,N,N-tetramethylethylenediamine to the black suspension is 5 g-20 g:100 mL, and the reaction is stirred at 50° C.-65° C. at a rotation speed of 100 rpm-180 rpm for 12 hours.
[0018] Another object of the present invention is to provide an application of the hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water bodies.
[0019] Furthermore, the method for using the hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water bodies comprises:
[0020] The hydrophobic biochar composite material is mixed with water containing hydrophobic pollutants and subjected to an oscillation treatment to complete the adsorption treatment of the hydrophobic pollutants in the water.
[0021] The use of the hydrophobic biochar composite material in the adsorption of hydrophobic pollutants in water bodies is characterized in that the mass volume ratio of the hydrophobic biochar composite material to the water body containing hydrophobic pollutants is 0.1g~1.0g:1L.
[0022] The use of the hydrophobic biochar composite material in the adsorption of hydrophobic pollutants in water bodies is characterized in that the pollutants are perfluorinated compounds, and the initial concentration of the pollutants in the pollutant-containing water body is 1 mg / L to 100 mg / L.
[0023] The application of the hydrophobic biochar composite material in the adsorption of hydrophobic pollutants in water bodies is characterized in that the temperature of the oscillation treatment is 20°C to 35°C, the rotation speed of the oscillation treatment is 150rpm to 200rpm, and the time of the oscillation treatment is 0.5h to 24h.
[0024] In combination with all the above-mentioned technical solutions, the advantages and positive effects possessed by the present invention are as follows: the hydrophobic biochar composite material provided by the present invention includes biochar, and the surface of the biochar is modified with a copolymer of sulfobetaine and acrylamide. In the present invention, the copolymer of sulfobetaine and acrylamide not only contains a large number of protonated groups, but also can respond to changes in temperature, and its chain conformation undergoes drastic changes, showing hydrophobicity at room temperature. The copolymer is prepared by reacting acrylamide with [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide, and is used to modify biochar, which is beneficial to changing the hydrophobicity of the adsorption material, improving the adsorption capacity of hydrophobic pollutants, and expanding the application of biochar materials in treating polluted water bodies. The hydrophobic biochar composite material of the present invention has the advantages of hydrophobicity, strong adsorption capacity, high practical application value, etc. It can be used to adsorb hydrophobic pollutants in water bodies and is a very promising new biochar material.
[0025] In the hydrophobic biochar composite material of the present invention, the hydrophilicity and hydrophobicity of the biochar are changed due to the modification of the copolymer of sulfobetaine and acrylamide. The higher the content of the copolymer of sulfobetaine and acrylamide on the surface of the biochar, the stronger the hydrophobicity of the biochar surface, the stronger the hydrophobic effect between the biochar and the hydrophobic pollutants, and thus the better the adsorption and removal effect of the hydrophobic pollutants.
[0026] The present invention also provides a method for preparing a hydrophobic biochar composite material, using acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide as raw materials, ammonium persulfate as an initiator, and N,N,N,N-tetramethylethylenediamine as an accelerator, preparing a copolymer of sulfobetaine and acrylamide and modifying it on the surface of biochar by physical adsorption and chemical action, specifically, putting biochar into a mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide, passing nitrogen gas for deoxygenation, and then adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine for reaction to generate a copolymer of sulfobetaine and acrylamide, and loading it on the surface of biochar. It can be seen that the preparation method of the present invention has the advantages of simple process, easy operation, mild and easy-to-control reaction conditions, low cost, short time consumption, etc., is suitable for continuous large-scale batch production, and is convenient for industrial utilization.
[0027] The present invention also provides an application of a hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water bodies. By mixing the hydrophobic biochar composite material with the hydrophobic pollutants and performing an oscillation treatment, the adsorption treatment of the hydrophobic pollutants in the water body can be achieved. Taking a water body containing perfluorinated compounds as an example, the hydrophobic biochar composite material of the present invention has a strong adsorption capacity for perfluorinated compounds in the water body. When the initial concentration of perfluorinated compounds in the water body is 10 mg / L, the adsorption amount is increased by more than 140% compared with the original biochar. The hydrophobic biochar composite material of the present invention has a significant effect on the adsorption and removal of hydrophobic pollutants in water bodies, is suitable for the repair of polluted water bodies, can achieve the effective removal of hydrophobic pollutants, has a high application value in the treatment of polluted water bodies, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 It is a flow chart of the method for preparing the hydrophobic biochar composite material provided in an embodiment of the present invention.
[0030] Figure 2 This is a SEM image of the hydrophobic biochar composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] In view of the problems existing in the prior art, the present invention provides a hydrophobic biochar composite material and a preparation method thereof. The present invention is described in detail below in conjunction with the accompanying drawings.
[0033] The hydrophobic biochar composite material provided by the embodiment of the present invention includes biochar, and the surface of the biochar is modified with a copolymer of sulfobetaine and acrylamide.
[0034] like Figure 1 As shown, the method for preparing the hydrophobic biochar composite material provided by the embodiment of the present invention comprises the following steps:
[0035] S101, preparing a mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide;
[0036] S102, adding biochar to the mixed solution obtained in S101 to react and obtain a black suspension;
[0037] S103, reacting the black suspension obtained in S102 with ammonium persulfate and N,N,N,N-tetramethylethylenediamine to obtain a hydrophobic biochar composite material.
[0038] The method for preparing the hydrophobic biochar composite material provided by the present invention can also be implemented by other steps by ordinary technicians in the industry. Figure 1 The method for preparing the hydrophobic biochar composite material provided by the present invention is only a specific embodiment.
[0039] The raw biochar used in the following examples is homemade, and the other materials and instruments are commercially available. In the examples of the present invention, unless otherwise specified, the process used is a conventional process, the equipment used is a conventional equipment, and the data obtained are the average values of more than three tests.
[0040] The technical solution of the present invention is further described below in conjunction with embodiments.
[0041] Example 1
[0042] The hydrophobic biochar composite material provided by the embodiment of the present invention includes sawdust biochar, and the surface of the sawdust biochar is modified with a copolymer of sulfobetaine and acrylamide.
[0043] The method for preparing the hydrophobic carbon composite material in the above embodiment provided by the embodiment of the present invention comprises the following steps:
[0044] (1) The sawdust was washed with deionized water and then dried at 70°C for 24 hours. The dried sawdust was crushed and sieved (0.15 mm to 0.25 mm) and then placed in a tubular furnace for pyrolysis and calcination. During the pyrolysis process, the quartz tube of the tubular furnace was kept sealed and N2 was introduced into the tube at a flow rate of 200 mL / min to maintain anaerobic conditions throughout the pyrolysis process. The temperature rise program of the tubular furnace was set as follows: heating from room temperature to 600°C at a heating rate of 3°C / min, and pyrolysis was continued at this temperature for 2 hours, and then a natural cooling process was started. During the cooling process, N2 was continuously introduced at the same flow rate. After cooling to room temperature, the original biochar was taken out and the biochar was sieved to obtain biochar powder (0.15 mm to 0.25 mm).
[0045] (2) preparing 100 mL of a mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonate propyl)ammonium hydroxide, wherein the mass ratio of acrylamide to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonate propyl)ammonium hydroxide is 10 g:15 g;
[0046] (3) adding 5 g of biochar to the mixed solution in step (2), stirring at 35° C. and 150 rpm for 12 hours, introducing N2 into the solution at a flow rate of 100 mL / min, and stirring at 35° C. and 180 rpm for 1 hour to obtain a black suspension;
[0047] (4) Add 5 mg of ammonium persulfate to the black suspension in step (3), stir at 60° C. and 120 rpm for 12 hours, filter and collect the solid, and dry the solid to obtain a hydrophobic biochar composite material.
[0048] The hydrophobic biochar composite material prepared in Example 1 of the present invention has a black powder appearance. The hydrophobic biochar composite material prepared in Example 1 of the present invention was observed under a scanning electron microscope. The results are as follows: Figure 2 shown. Figure 2 This is a SEM image of the hydrophobic biochar composite material of the present invention.
[0049] Example 2
[0050] The application of the hydrophobic biochar composite material provided in an embodiment of the present invention in adsorbing hydrophobic pollutants in water, specifically in adsorbing perfluorinated compounds in water, comprises the following steps:
[0051] According to the mass volume ratio of the hydrophobic biochar composite material to the water body (containing the aqueous solution of perfluorinated compounds) of 0.1g:1L, four portions of the hydrophobic biochar composite material prepared in Example 1 were weighed, and added to a solution containing perfluorooctane sulfonic acid (hereinafter referred to as PFOS) and perfluorooctanoic acid (hereinafter referred to as PFOA) at a concentration of 10mg / L (the volume of the solution was 100mL), mixed evenly, and subjected to constant temperature oscillation treatment at a speed of 180rpm and a temperature of 25°C for 24h to complete the treatment of the aqueous solution containing perfluorinated compounds. After the oscillation treatment, the solution was allowed to stand and precipitated, and the supernatant was taken to determine the concentration of perfluorinated compounds by HPLC-HRMS / MS, and the adsorption amount of perfluorinated compounds by the hydrophobic biochar composite material was calculated, and the results are shown in Table 1. The unmodified original biochar was used as a control and was used to adsorb perfluorinated compounds in the water body under the same conditions. The adsorption amount of perfluorinated compounds by the original biochar is shown in Table 1.
[0052] Table 1 Adsorption removal rate of perfluorinated compounds in water by different materials
[0053] PFOS PFOA Raw biochar 39.1% 40.7% Hydrophobic biochar composites 99.8% 98.6%
[0054] From the results in Table 1, it can be seen that compared with the original biochar, the hydrophobic biochar composite material prepared in Example 1 of the present invention has a significantly increased adsorption capacity for perfluorinated compounds in aqueous solution. When the initial concentration of perfluorinated compounds is 10 mg / L, the adsorption removal rate of perfluorinated compounds in water by the hydrophobic biochar composite material of the present invention is increased by more than 140% compared with the original biochar, indicating that the copolymer of sulfobetaine and acrylamide modified on the surface of biochar in the present invention has a significant enhancing effect on improving the ability of biochar to adsorb hydrophobic pollutants.
[0055] In the present invention, the copolymer of sulfobetaine and acrylamide is used to modify biochar, which is beneficial to improving the adsorption capacity of the adsorption material and expanding the application of biochar materials in polluted water bodies. The hydrophobic biochar composite material of the present invention has the advantages of stable structure, strong adsorption capacity, high practical application value, etc., and is a very promising new biochar material. The hydrophobic biochar composite material of the present invention has a significant effect on the adsorption and removal of hydrophobic pollutants in water bodies, is suitable for the repair of polluted water bodies, has a high application value in the treatment of polluted water bodies, and has broad application prospects.
[0056] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for using a hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water, characterized in that: include: The hydrophobic biochar composite material is mixed with water containing hydrophobic pollutants and subjected to oscillation treatment to complete the adsorption treatment of the hydrophobic pollutants in the water; The hydrophobic biochar composite material comprises biochar, and the surface of the biochar is modified with a copolymer of sulfobetaine and acrylamide; The preparation method of the hydrophobic biochar composite material comprises: Step 1, preparing a mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide; in the mixed solution of acrylamide and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide, the mass volume ratio of acrylamide to water is 10g-20g:100mL, and the mass volume ratio of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide to water is 10-40g:100mL; Step 2: adding biochar to the mixed solution obtained in step 1 to obtain a black suspension; the mass volume ratio of the biochar to the mixed solution is 10-20 g: 100 mL; after mixing, stirring at 20° C. to 40° C. at a rotation speed of 160 rpm to 180 rpm for 6 to 24 hours; Step 3, introducing nitrogen into the black suspension obtained in step 2 for half an hour; specifically, introducing 100 mL to 200 mL / min of nitrogen into the mixed solution and stirring at 50 to 60° C. at a rotation speed of 120 rpm to 180 rpm for 0.5 to 2 hours; Step 4, adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to the black suspension obtained in step 3 for reaction, wherein the mass volume ratio of ammonium persulfate to the black suspension is 2mg~20mg:100mL, and the mass volume ratio of N,N,N,N-tetramethylethylenediamine to the black suspension is 5g~20g:100mL, and the reaction is stirred at 50°C~65°C at a rotation speed of 100rpm~180rpm for 12h to obtain a hydrophobic biochar composite material.
2. The method for using the hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water according to claim 1, characterized in that: The mass volume ratio of the hydrophobic biochar composite material to the water body containing hydrophobic pollutants is 0.1g-1.0g:1L.
3. The method for using the hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water according to claim 1, characterized in that: The hydrophobic pollutant is a perfluorinated compound, and the initial concentration of the pollutant in the water body containing the hydrophobic pollutant is 1 mg / L to 100 mg / L.
4. The method for using the hydrophobic biochar composite material in adsorbing hydrophobic pollutants in water according to claim 1, characterized in that: The temperature of the oscillation treatment is 20° C. to 35° C., the rotation speed of the oscillation treatment is 150 rpm to 200 rpm, and the time of the oscillation treatment is 0.5 h to 24 h.
Citation Information
Patent Citations
Cationic polyacrylamide modified biochar composite material and preparation method thereof
CN113145085A